Pengaruh Religiusitas dan Demografi Santri Pondok Pesantren Jagad „Alimussirry Terhadap Minat Membayar Zakat Melalui Lembaga Amil Zakat - Arilia, Linawati; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2019)
This study aims to analyze the effect of the religious and demographic of the santri of 'Alimussirry Islamic Boarding School on the interest in paying zakat at the zakat institutions. The independent variables in this study consisted of two variables, namely the religiosity variables and demographic variables. Religiosity variables are measured using dimensions of worship, belief, religious knowledge, appreciation and practice. While demographic variables are measured using indicators of age, work experience and income. The analysis technique used is multiple linear regression analysis. The results of this study are the variables of religiosity santri of Islamic Boarding School affect the interest of paying zakat at the zakat institution. This is because santri have knowledge of religion more than people who are not educated in a boarding school environment. The demographic variable of the Islamic Boarding School 'Alimussirry affects the interest in paying zakat in the zakat institution, but the influence of this demographic variable is very low because santri does not have income and does not have more work experience. In addition, the young age also affect a person in donating his property.